DOP16 Categorizing endoscopic severity of Crohn's Disease using the Modified Multiplier SES-CD (MM-SES-CD). (21st January 2022) - Narula, N; Pray, C; Wong, E; Colombel, J F; Marshall, J; Daperno, M; Reinisch, W; Dulai, P
Abstract: Background: Current endoscopic scoring indices such as the Simple Endoscopic Score for Crohn's Disease (SES-CD) quantify the degree of mucosal inflammation in Crohn's disease (CD) but lack prognostic potential. The Modified Multiplier of the Simple Endoscopic Score for Crohn's Disease (MM-SES-CD) is an internally validated endoscopic scoring tool that quantifies the endoscopic burden of CD and can be accessed online (https://www.mcmasteribd.com/mm-ses-cd ). 1 This analysis aims to establish thresholds of the MM-SES-CD that classify CD endoscopic burden into inactive or very mild disease, mild, moderate, and severe disease based on the probability of achieving endoscopic remission (ER) on active therapy at one-year. Methods: This post-hoc analysis included pooled data from three CD clinical trials (n=350 patients, baseline SES-CD ≥3 with confirmed ulceration). Maximum Youden Index calculations were used to determine thresholds for severity. Chi-square tests of trend were used to compare achievement of ER between severity categories, and Kaplan-Meier survival curve analysis was used to compare time to clinical remission (CR). Results: Table 1 demonstrates the baseline characteristics of the 350 participants included in this analysis. MM-SES-CD severity categories were established as inactive or very mild (score <14), mild (score ≥14 to <31), moderate (≥31 to <45), and severe (score ≥45), which were predictive of one-year ER (50%, 30.3%, 21.7%, 8.8% respectively p<0.001) (Table 2). Lower MM-SES-CD scores had numerically higher rates of one-year CR, and time to CR over 52 weeks was superior to those with higher scores (p=0.0492) (Figure 1). MM-SES-CD thresholds for the achievement of ileal ER at one-year among 75 patients with isolated ileal disease were also established as mild (score <14), moderate (score ≥14 to <33), and severe (score ≥33), which were predictive of one-year ER (66.7%, 33.3%, 13.3%, respectively p=0.027) (Table 3). Conclusion: We have established numerical cut-offs of the MM-SES-CD that categorize endoscopic disease severity and are prognostic for one-year ER and CR. These cut-offs could help ensure adequate balance between study arms (e.g. in prevalence of mild or moderate endoscopic disease) and identify patients with severe endoscopic disease and low probability of achieving ER. Reference: 1. Predicting endoscopic remission in Crohn's disease by the modified multiplier SES-CD (MM-SES-CD). Gut, 2021: p. gutjnl-2020–323799.